Opioid analgesics increase incidence of somnolence and dizziness as adverse effects of pregabalin: a retrospective study - Ohishi, Akihiro; Chisaki, Yugo; Hira, Daiki; Nagasawa, Kazuki; Terada, Tomohiro (Journal of pharmaceutical health care and sciences, 2015)
Background Pregabalin, a gabapentinoid, is an adjuvant analgesic for treatment of neuropathic pain, but it has serious adverse effects such as somnolence and dizziness, particularly in elderly patients. Although decreased renal function is considered to the contributing factor for high frequency of these adverse effects in elder patients, only a few systematic clinical investigations, especially for hospitalized patients, have been performed on factors that might affect the incidence of its adverse effects. In this study, we performed a retrospective study on the effect of concomitant drugs on induction of somnolence and dizziness as adverse effects of pregabalin in hospitalized patients. Methods The subjects were all pregabalin-administered patients in Shiga University of Medical Science Hospital from September 2010 to September 2012, and the subject number was 195. Multivariate logistic regression analysis was performed to determine predictors of the adverse effects, creatinine clearance, duration of pregabalin therapy, initial and maintenance doses of pregabalin, and concomitant drugs, including hypoglycemic drugs, anti-hypertensive ones, non-steroidal anti-inflammatory ones, opioids and central nervous system depressants, being used as independent variables. Results The median initial doses of pregabalin in each renal function group were the same with the case of the defined dose. Although renal function is a well-known factor for prediction of development of adverse effects of pregabalin, we did not detect significant contribution of it. Alternatively, it was demonstrated that concomitant administration of opioids was the significant factor of the incidence of somnolence and dizziness. The first onset date of the adverse effects was frequently detected in the early days of the pregabalin therapy. Conclusions The fine tuning of pregabalin dosage schedule based on the renal function appeared to be critical for prevention of development of its adverse effects. Adverse effects tended to develop in the initial phase of pregabalin therapy. Concomitant administration of opioids with pregabalin has the potential to increase the incidence of adverse effects, and thus much more careful attention has to be paid especially in those situations.